(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The governorate of Lattakia has Four Marine fishing ports on the eastern Mediterranean Cost. But the natural characteristics of this Cost such like (geomorphological continental shelf ,water characteristics ) leads to the limitation of the quantities of biomass and the various of volume of marine fishing from port to another. This study shows that the continental shelf north Lattakia is more dip than it is in the South ,the degree of Salinity,Oxygen,Temperature is nearly similar on all marine sectors, and the sector fished next toLattakia port provides the most big fishing product because of favourable depth and the good quantity of plankton. Person Coefficient indicate a strong positive Correlation (+0.64) between the quantities of production and the degree of Oxygen dissolved, whereas the coefficient indicate a strong negative Correlation (-0.65) with Salinity degree. تمتلك محافظة اللاذقية أربع موانئ لّلصيد البحري على السَّاحل الشَّرقي للبحر المتوسط. ولكن الخصائص الطَّبيعية لساحلها (كمورفولوجية الأعماق وخصائص المياه) أثرت على كميات الأسماك واختلاف حجم الصَّيد البحري بين ميناء وآخر. بيَّنَتْ الدِّراسة أنَّ الرَّصيف القاري لشمال مدينة اللاذقية أكثر عمقاً مما عليه جنوبها. وأنَّ درجات الملوحة والأوكسجين والحرارة متقاربة جداً على جميع القِّطاعات وأنَّ قطاع الصَّيد المقابل لميناء اللاذقية يؤمن الكمية الأكبر من إنتاج الصَّيد البحري لتوفر أعماق مناسبة وكميات بلانكتون. يشير معامل بيرسون أنَّ العلاقة بين كميات الإنتاج والأكسجين طردية وقوية(+0.64). بينما يشير إلى علاقة عكسية قوية مع درجة الملوحة(-0.65).